2011
DOI: 10.1017/s1751731111001145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a linseed diet on lipogenesis, fatty acid composition and stearoyl-CoA-desaturase in rabbits

Abstract: The aim of the study was to examine the effect of a linseed diet on meat quality and on lipogenesis in rabbits. Twelve rabbits were fed a control or a linseed diet. There was no diet effect on growth, food consumption, carcass characteristics and meat ultimate pH and colour. Feeding the linseed diet increased the n-3 polyunsaturated fatty acids (PUFA) levels in perirenal and interscapular fats, in the Longissimus dorsi muscle and in the liver. The linseed diet produced lower linoleic acid/a-linolenic acid rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
17
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 40 publications
11
17
1
1
Order By: Relevance
“…In the current study, growth performance of broiler chickens in days 21-42 and 1-42 of treatment was in line with previous reports that the substitution of some (Olomu and Baracos 1991) or all (Benatmane et al 2011) dietary oil with FO did not significantly affect weight gain, feed consumption, and feed efficiency. The study of Rahimi et al (2011) showed that BW gain during days 1-21 did not differ by feeding 7.5% FO, but it decreased with adding the amount of 10%, which is completely opposite to our result of the elevated BW gain at 21 days by FO1 treatment (replacing 1.25% CO by FO).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the current study, growth performance of broiler chickens in days 21-42 and 1-42 of treatment was in line with previous reports that the substitution of some (Olomu and Baracos 1991) or all (Benatmane et al 2011) dietary oil with FO did not significantly affect weight gain, feed consumption, and feed efficiency. The study of Rahimi et al (2011) showed that BW gain during days 1-21 did not differ by feeding 7.5% FO, but it decreased with adding the amount of 10%, which is completely opposite to our result of the elevated BW gain at 21 days by FO1 treatment (replacing 1.25% CO by FO).…”
Section: Discussionsupporting
confidence: 92%
“…Different fatty acid deposition and a lower ratio of n-6/n-3 PUFA in the tissue of bull, rabbit, pig, broiler muscles, and eggs of hens were also achieved by changing the source of dietary fat (Raes et al 2004;Herdmann et al 2010;Oliveira et al 2010;Benatmane et al 2011). In recent years, interest has been focused on the effect of the dietary fat source on the fatty acid deposition in pig, salmon, rabbit liver, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in plasma (Table 6), and particularly in liver (Table 5), the difference in n-6 content between rabbit and chicken samples was less pronounced than in feeds (P , 0.05). Variations in the digestion process between species, their FA metabolic sites and in the activity of enzymes involved in FA metabolism between species might explain these differences (Benatmane et al, 2011;Kouba and Mourot, 2011). Furthermore, the tendency of rabbit liver to incorporate higher PUFA than chicken is consistent with our findings in animals receiving a diet that was richer in SFA, supplied through hydrogenated palm FA distillates (Tres et al, 2012).…”
Section: Resultssupporting
confidence: 84%
“…The ultimate pH in our study was in the normal range for rabbit meat (Blasco and Piles, 1990). These results are in agreement with those reported by Benatmane et al (2011), Dal Bosco et al (2012 and Peiretti et al (2011a and with different raw material supplementation in rabbit feed. In our study, meat colour parameters were not affected significantly by AB supplementation.…”
Section: Carcass Characteristicssupporting
confidence: 93%